Les conseillers pédagogiques de l’enseignement supérieur entre unité et variété : étude clinique - Jean-Pierre Bourgade (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
In a clinical approach, based on the Anthropological theory of the didactical, we study the different ways the members of a network of faculty developers seize a tool designed for the analysis of teaching. Thanks to a praxeological model of this tool, we analyse some of its misuses. This analysis leads to the following assumption: different faculty developers have distinct forms of interests, which may explain differences in the uses of the analysis tool. This indicates that the building of the profession of faculty developer certainly relies on the production of an interest specific to faculty developers.